1997
DOI: 10.1037/0033-2909.122.1.38
|View full text |Cite
|
Sign up to set email alerts
|

What do men want? Gender differences and two spheres of belongingness: Comment on Cross and Madson (1997).

Abstract: In response to S. E. Cross and L. Madson's (1997) suggestion that men's behaviors reflect a desire for independence and separateness, the authors propose that those same behaviors are designed to form connections with other people but in a broader social sphere. Women's sociality is oriented toward dyadic close relationships, whereas men's sociality is oriented toward a larger group. Gender differences in aggression, helping behavior, desire for power, uniqueness, self-representations, interpersonal behavior, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
362
6
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 465 publications
(390 citation statements)
references
References 29 publications
18
362
6
4
Order By: Relevance
“…Men may not have excluded relationships from their broader ideological sphere (Baumeister & Sommers, 1997;Gabriel & Gardner, 1999), allowing them to forge connections between their political beliefs and their relationship beliefs that women may be less likely to make. To the extent this is so, when participants are focused on their own personal relationships, an association between system-related motivations and committed relationships may exist for women.…”
Section: Resultsmentioning
confidence: 99%
“…Men may not have excluded relationships from their broader ideological sphere (Baumeister & Sommers, 1997;Gabriel & Gardner, 1999), allowing them to forge connections between their political beliefs and their relationship beliefs that women may be less likely to make. To the extent this is so, when participants are focused on their own personal relationships, an association between system-related motivations and committed relationships may exist for women.…”
Section: Resultsmentioning
confidence: 99%
“…The sociocultural perspective suggests that women find close interpersonal relationships more important for defining their self concept compared to men (Cross & Madson, 1997), whereas men tend to value groups in defining their self concept (Baumeister & Sommer, 1997)-and this perspective predicts relatively greater male cooperation in larger groups (Gabriel & Gardner, 1999). An evolutionary perspective suggests that men should be more cooperative than women in larger groups, because men have more to gain (and less to lose) from interacting with many other individuals for the purpose of trading and warfare ).…”
Section: Group Sizementioning
confidence: 99%
“…The sociocultural perspective suggests that sex differences in social roles may result in sex differences in the importance of close relationships and group memberships in defining women's and men's self-concepts, respectively (Baumeister & Sommer, 1997;Cross & Madson, 1997). An implication of this perspective is that women may be more cooperative in social dilemmas involving close interpersonal dyadic interactions, and men may be more cooperative than women in larger group social dilemmas.…”
Section: Group Size and Cooperationmentioning
confidence: 99%
“…Such relational competences seem not equally divided across the two sexes in that they are also shaped by genetics (Baron-Cohen, 2002;Seeley, Gardner, Pennington, & Gabriel, 2003). Research has shown that, compared to men, women relate less often to highly abstract entities, such as groups, institutions, and organizations (Baumeister & Sommer, 1997;Gabriel & Gardner, 1999) because they are less equipped in predicting the behavior of systems (Baron-Cohen, 2002). Given that some resource extensions, such as capital, can often only be accessed through relationships with institutions such as banks, women may face greater challenges in accessing such resource extensions.…”
Section: Resultsmentioning
confidence: 99%